Current evidence of antibiotics as adjunctive therapy in peri-implant diseases: a review (2023)
Introduction: Dental implants are a reliable and commonly used procedure in clinical practice for replacing missing teeth. Nevertheless, they are not free of complications, with peri-implant mucositis and peri-implantitis being possible issues that can arise. Different treatments have been suggested to both prevent and manage peri- implant diseases. These therapeutic approaches encompass non-surgical and surgical methods, and numerous adjunctive therapies have been proposed to potentially enhance their effectiveness, leading to clinical and microbiological improvements in these conditions. Methods: A comprehensive literature review was carried out, involving recent articles of scientific significance obtained through searches in various indexed databases, including PubMed. Results: 35 articles that report that antibiotic therapy is a valid adjunctive alternative for peri-implantitis were found. Conclusions: The placement of dental implants can potentially result in future peri-implant diseases, and as of now, there is no definitive treatment guide available. Nevertheless, recent studies have highlighted the crucial role of eliminating bacterial biofilm from the implant surface in peri-implantitis treatment. This decontamination process, whether achieved through surgical or non-surgical methods, must be complemented with antimicrobial therapeutic approaches.